Perlindungan konsumen berdasarkan klausula baku dalam kontrak digital sebagai wujud kepatuhan terhadap undang-undang - Soediono, Ricardo; Doroh, Gasper; Hidayat, A. Taufiq; Afandi, M. Irfan (LP3M Universitas Islam Zainul Hasan Genggong, 2023)
Agreements found on online shopping websites, known as digital contracts, are binding for parties involved in electronic commerce. These include not only the business actors but also the platform providers acting as facilitators. Digital contracts often contain standard clauses unknowingly agreed upon by consumers. According to Article 1, point 17 of the ITE Law, electronic contracts are agreements made via electronic systems. Standard clauses are governed by Law No. 8 of 1999 on Consumer Protection. The rise of online commerce demands legal certainty to protect consumer rights. Consumer protection under the law ensures legal assurance for consumers in electronic transactions.